AN ISLAMIC SEARCH OF NOBLE VALUES: The Prevalence of Modern Principles and the Resilience of Local Traditions in Indonesian Daâwa - Suwarno, Peter (IAIN Walisongo Semarang, 2014)
AbstractThe variety of daâwa (Islamic preaching) in Indonesia indicated not only thediversity in Islamic groups and identities, but also the varieties and changes invalues and principles embraced by Indonesian Muslims. This paper argued thatthese daâwa activities constitute searches of most suitable Indonesian Islamicprinciples that inevitably include the negotiation of Islamic, global, and localvalues. For this purpose, this paper showed examples of various international andIndonesian Islamic scholars and leaders who help change social, political, andreligious rhetorical landscape through various arguments involving especiallyIslamic and modern-international values. This paper maintained that, in additionto Muslims exposure to modern global principles such as democracy and humanrights, the increasing popularity and resilience of local-traditional rituals, performances,and expressions in Indonesian daâwa have significantly shaped thesearch of the Indonesian Islamic noble values.***Keragaman dakwah Islam di Indonesia tidak hanya tampak dalam keragamankelompok serta identitas Islam, tetapi juga dalam varian dan perubahan nilai-nilaiserta prinsip-prinsip yang dianut oleh umat Islam Indonesia. Tulisan inimenegaskan bahwa kegiatan dakwah ini merupakan pencarian prinsip-prinsipIslam Indonesia yang paling sesuai yang mau tidak mau merupakan upayanegosiasi nilai Islam, global, dan nilai-nilai lokal. Untuk tujuan tersebut, tulisan inimenunjukkan beberapa contoh ulama dan pemimpin Islam internasional danIndonesia yang membantu mengubah landscape retorika sosial, politik dan agamamelalui berbagai argumen yang secara khusu melibatkan nilai-nilai Islam danmodern-internasional. Tulian ini berpendapat bahwa, disamping Muslim harusberhadapan dengan prinsip-prinsip global modern seperti demokrasi dan hakasasi manusia, meningkatnya popularitas dan ketahanan dari ritual, pertunjukan,dan ekspresi lokal-tradisional dalam dakwah Indonesia telah membentukpencarian nilai-nilai luhur Islam Indonesia secara signifikan.Keywords: daâwa, Islam, modernity, local-traditional rituals,noble values